Static performance analysis of single-layer steel cooling tower. (June 2019) - Ma, Hui-huan; Li, Shao-zhen; Fan, Feng
Abstract: For a hyperbolic steel-structure cooling tower, a single-layer reticulated shell system was designed. The static behaviors of the single-layer reticulated shell system were studied under different load combinations. By analyzing the stability of the system, a whole load-displacement curve of the structure was obtained, and a reasonable strengthening scheme was proposed. Taking the grid form and grid size as the optimization parameters, the single-layer reticulated shell system for a steel-structure cooling tower was optimized at heights of 90, 124, and 220 m. The static behaviors of the single-layer reticulated shell system with different parameters, including the quantity of steel, maximum displacement of the nodes, peak stress, and ultimate bearing capacity, were compared. The optimum grid form and grid size of the single-layer reticulated shell system under different heights were obtained.